Pelvic migration of the helical blade after treatment of transtrochanteric fracture using a proximal femoral nail() - Gomes, Pedro Luciano Teixeira (Rev Bras Ortop, 2016)
Proximal femoral nails with a helical blade are a new generation of implants used for treating transtrochanteric fractures. The blade design provides rotational and angular stability for the fracture. Despite greater biomechanical resistance, they sometimes present complications. In the literature, there are some reports of cases of perforation of the femoral head caused by helical blades. Here, a clinical case of medial migration of the helical blade through the femoral head and acetabulum into the pelvic cavity is presented.